Pisum sativum Response to Nitrate as Affected by Rhizobium leguminosarum-Derived Signals - Laure Boeglin; Marie-Christine Morère Le-Paven; Thibault Clochard; Joëlle Fustec; Anis M. Limami (Plants, 2022)
Legumes are suitable for the development of sustainable agroecosystems because of their ability to use atmospheric N2 through symbiotic nitrogen fixation (SNF). However, a basic NO3− input is necessary before SNF takes place to ensure successful seedling establishment. Since Rhizobia not only induce nodulation but also affect root branching by stimulating the development of lateral roots, and NO3− as a signal also modulates root system architecture, we investigated whether Rhizobium-derived signals interfere in nitrate signaling. Here, we bring evidence that (i) Rhizobium-altered NO3−-mediated processes in pea expressions of major players in NO3− transport, sensing, and signaling were affected, and (ii) the characteristic limitation of root foraging and branching in response to NO3− supply was abolished. The number of tertiary roots per secondary root was higher in infected compared to uninfected peas, thus indicating that the Rhizobium effect allows for favorable management of trade-offs between nodules growth for nitrogen capture and root foraging for water and other nutrient uptake in pea. The outcome of this basic research can be used to produce molecular tools for breeding pea genotypes able to develop deep-foraging and branched root systems, and more competitive architectures and molecular levels for soil NO3− absorption during seedling establishment without jeopardizing nodulation.